Oral Storytelling as Evidence of Pedagogy in Forager Societies - Scalise Sugiyama, Michelle (Frontiers in Psychology, 2017)
Teaching is reportedly rare in hunter-gatherer societies, raising the question of whether it is a species-typical trait in humans. A problem with past studies is that they tend to conceptualize teaching in terms of Western pedagogical practices. In contrast, this study proceeds from the premise that teaching requires the ostensive manifestation of generalizable knowledge: the teacher must signal intent to share information, indicate the intended recipient, and transmit knowledge that is applicable beyond the present context. Certain features of human communication appear to be ostensive in function (e.g., eye contact, pointing, contingency, prosodic variation), and collectively serve as “natural pedagogy.” Tellingly, the oral traditions of foraging peoples typically employ these and other ostensive behaviors, and are widely reported to be an important source of generalizable ecological and social knowledge. Despite this, oral storytelling has been conspicuously overlooked in studies of teaching in forager societies. Accordingly, this study presents evidence that oral storytelling involves the use of ostension and the transmission of generic knowledge, thereby meeting the criteria of pedagogy.